Giant lipoma with malignant mesenchymal component in right arm: a rare presentation - Ray, Awadhesh A.; Ray, Aniket A. (International Surgery Journal, 2022)
Lipomas are commonly found benign tumors of the adipocytes, which can vary in size greatly and can be present anywhere in the body where there is fat, therefore it is also known as universal tumor. These can produce symptoms by compressing nearby structures or can be asymptomatic and only cause cosmetic problems. We presented a case of a 64 years old male patient who presented with a huge swelling in the right arm occupying its medial, posterior and lateral aspects. It was asymptomatic but was causing disfigurement of the right arm and therefore the patient wanted it removed. Excision of the lipoma was done under general anesthesia, and there were 2 giant lipomatous masses 14 by 17 and 10 by 13 cm. Histopathology report showed it to have malignant mesenchymal components. Giant lipomas are more likely to show malignant conversion, therefore it should always be sent for histopathological examination. Preoperative radiological examination in giant lipomas help in defining the extent of involvement of the tumor and helps in better surgical decision making.